ROS-Driven Oxidative Modification: Its Impact on Chloroplasts-Nucleus Communication - Kim, Chanhong (Frontiers in Plant Science, 2020)
As a light-harvesting organelle, the chloroplast inevitably produces a substantial amount of reactive oxygen species (ROS) primarily through the photosystems. These ROS, such as superoxide anion, hydrogen peroxide, hydroxyl radical, and singlet oxygen, are potent oxidizing agents, thereby damaging the photosynthetic apparatus. On the other hand, it became increasingly clear that ROS act as beneficial tools under photo-oxidative stress conditions by stimulating chloroplast-nucleus communication, a process called retrograde signaling (RS). These ROS-mediated RS cascades appear to participate in a broad spectrum of plant physiology, such as acclimation, resistance, programmed cell death (PCD), and growth. Recent reports imply that ROS-driven oxidation of RS-associated components is essential in sensing and responding to an increase in ROS contents. ROS appear to activate RS pathways via reversible or irreversible oxidation of sensor molecules. This review provides an overview of the emerging perspective on the topic of 'oxidative modification-associated retrograde signaling'.